2021
DOI: 10.3390/cells10102747
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Inherent Niches in 3D Multicellular MSC Spheroids Reconfigures Metabolism and Enhances Therapeutic Potential

Abstract: Multicellular spheroids show three-dimensional (3D) organization with extensive cell–cell and cell–extracellular matrix interactions. Owing to their native tissue-mimicking characteristics, mesenchymal stem cell (MSC) spheroids are considered promising as implantable therapeutics for stem cell therapy. Herein, we aim to further enhance their therapeutic potential by tuning the cultivation parameters and thus the inherent niche of 3D MSC spheroids. Significantly increased expression of multiple pro-regenerative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…It has been shown that MSC paracrine properties can be modulated by some preconditioning methods, including the growing of MSCs under three-dimensional (3D) culture conditions. Indeed, in response to 3D MSC priming/activation, the production of factors is switched toward a more anti-inflammatory and pro-trophic phenotype that results in an improvement in MSC therapeutic properties [21,[34][35][36]. Our previous studies have shown that preconditioning of MSCs by 3D cultures enhances the secretion of functional factors.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that MSC paracrine properties can be modulated by some preconditioning methods, including the growing of MSCs under three-dimensional (3D) culture conditions. Indeed, in response to 3D MSC priming/activation, the production of factors is switched toward a more anti-inflammatory and pro-trophic phenotype that results in an improvement in MSC therapeutic properties [21,[34][35][36]. Our previous studies have shown that preconditioning of MSCs by 3D cultures enhances the secretion of functional factors.…”
Section: Introductionmentioning
confidence: 99%
“…Cell-based assays, including those able to mimic physiological phenomena, are important because, for instance, stem cell therapies showed promise for treating various injuries and diseases [24]. The strategies that can improve the effectiveness of drugs and nanomaterials and decrease the observed therapeutic variability are necessary for biomedical applications.…”
Section: Resultsmentioning
confidence: 99%
“…The strategies that can improve the effectiveness of drugs and nanomaterials and decrease the observed therapeutic variability are necessary for biomedical applications. Recently, scientists generated differently sized stem cell spheroids by controlling the cell number and the cultivation parameters to the estimation of matrix components value, including fibronectin, laminin, and collagen [24]. Their results revealed that expression of the mentioned molecules and immunomodulatory factors significantly altered between the different sizes of the spheroids, corresponding to the metabolic activity of the spheroids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations